Corporate Compliance and the Antitrust Agencies’ Bi-Modal Penalties - Calkins, Stephen (1997)
Calkins discusses individual compared with entity penalties as tools for encouraging corporate law compliance and comments on the relationship between monetary payments as compensation and deterrence